2004
DOI: 10.1038/sj.bjp.0706016
|View full text |Cite
|
Sign up to set email alerts
|

KATP‐channel‐induced vasodilation is modulated by the Na,K‐pump activity in rabbit coronary small arteries

Abstract: 1 The purpose of the study was to evaluate the importance of the Na,K-pump in relaxations induced by K ATP -channel openers in rabbit coronary small arteries. 2 Arterial segments were mounted in myographs for recording of isometric tension. Whole-cell patch clamp was used to assess K ATP -channel currents in isolated smooth muscle cells from the arteries. 3 In arteries preconstricted with the thromboxane A 2 analogue U46619 pinacidil and cromakalim induced concentration-dependent relaxations. In arteries preco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
3
13
2
Order By: Relevance
“…Moreover, adenosine has been reported to activate K ATP channels in rabbit mesenteric arteries and isolated coronary artery SMCs (58,65). Others have demonstrated the presence of K ATP channels on coronary arteries and coronary artery SMCs (28,65) and their role in A 2A -induced effects in reactive hyperemia and retinal microvessel dilation (5,33,77). However, there are no reports, to our knowledge, suggesting the involvement of K ATP channels in A 2A AR-and A 2B ARinduced changes in mouse CF.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Moreover, adenosine has been reported to activate K ATP channels in rabbit mesenteric arteries and isolated coronary artery SMCs (58,65). Others have demonstrated the presence of K ATP channels on coronary arteries and coronary artery SMCs (28,65) and their role in A 2A -induced effects in reactive hyperemia and retinal microvessel dilation (5,33,77). However, there are no reports, to our knowledge, suggesting the involvement of K ATP channels in A 2A AR-and A 2B ARinduced changes in mouse CF.…”
Section: Discussionmentioning
confidence: 58%
“…However, A 2B AR-induced vasodilatation is both nitric oxide dependent and independent in the mouse aortic conduit artery and coronary arteries, respectively (1,69). Although ATPsensitive K ϩ (K ATP ) channels have been shown to be present in coronary artery cells (28,65) and K ϩ channels, in general, are known to be involved in the A 2A AR and A 2B AR-mediated hyperpolarization of coronary arteries (31,39,52), the involvement of K ATP channels in adenosine-induced coronary artery responses remains poorly understood.…”
Section: Sanjani Ms Teng B Krahn T Tilley S Ledent C Mustafa Sjmentioning
confidence: 99%
“…We have previously demonstrated a functional interaction between ouabain-sensitive Na ϩ /K ϩ -pumps and K ATP channels. 37 In that study we found that the activity of ouabain-sensitive Na ϩ /K ϩ -pumps could modify the activity of the K ATP channels. The data in the present study suggest that K ATP channels provide K ϩ for the Na ϩ /K ϩ -pump under [K ϩ ] o -free conditions.…”
Section: Intervention Inmentioning
confidence: 96%
“…This mode of regulation may become more pronounced with aging, since glycolytic inhibition in aged rat hearts causes action potential shortening and arrhythmias that can be prevented by K ATP channel block with glibenclamide (575). Competition for local glycolytically derived ATP may also be responsible for the known functional interaction between the K ATP channel and the Na ϩ /K ϩ pump, which has been observed in several tissues, including frog skin (829), neurons (8), the kidney (548), skeletal muscle (663), smooth muscle (269), and the heart (411,646). Although the physiological relevance of this functional interaction is obvious, it has been suggested to be important in the protective effects of ischemic preconditioning (IPC) (331).…”
Section: Metabolic Enzymesmentioning
confidence: 99%